Penilaian Stabilitas Lereng dengan Perkuatan Akar Menggunakan Analisis Batas Elemen Hingga - Dio Alif Hutama; Himatul Farichah (LPPM Universitas Negeri Jakarta, 2024)
Slope instability poses serious threats to infrastructure and environmental sustainability. As a result, numerous reinforcement techniques have been used as disaster mitigation attempts to prevent slope failure. Among various traditional slope reinforcement methods, the use of vegetion root is more cost-effective and environmentally friendly. This paper presents stability assessment of root-reinforced slopes. Firstly, slope models were built for case of bare and root-reinforced slopes. The slope angles were varied in the range of 15º 55 º. The root cohesion and depth of root zone were adjusted within the ranges of 0 20 kPa and 0 1.5 m, respectively. The strength reduction finite element limit analysis method was applied to evaluate the stability of the slopes in this study. The results indicate that factor of safety increases with the increasing of root cohesion and depth of root zone. The best factor of safety was obtained for the case with root cohesion and depth of root zone of 20 kPa and 1.5 m, respectively. Shear dissipation contours of the slope models also show that root reinforcement reduces shear dissipation energy along the failure surface, consequently lowering the possibility of slope failure.